Study of the Influence of Nb2O5 in ZnO Solar Cells - Valerio, Tatiana Lima; Maia, Guilherme Arielo Rodrigues; Viomar, Aline; Dias, Bianca Vanjura; Rodrigues , Paulo Rogério Pinto (Orbital: The Electronic Journal of Chemistry, 2018)
The solar cells of semiconductors oxides have been largely studied. The zinc oxide (ZnO) and niobium oxide (Nb2O5) used in this work presented important physical-chemical characteristics in use of photovoltaic devices. The Nb2O5 presents the capacity of minimizing effects of charge recombination in the process of energetic conversion of solar cells. The oxides used in this work were characterized by the technique X-ray diffraction. The solar cells containing 5% of Nb2O5 presented of best results in a relationship of the electron transfer process, reaching the efficiency of 0.42%.DOI: http://dx.doi.org/10.17807/orbital.v10i3.1106